KONSISTENSI PENDIDIKAN PESANTREN - Abdul Karim Mansur (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2013)
The success of pesantren in delivering the students have an integral knowledge, piety attitude, politeness behavior, independence, and sincerity, a simbol that is recognized and powerful embedded in society. In his journey, many aspects of being teased between maintaining the character of Islamic tradition with a desire to follow the demands of change. Understanding the need to formulate the essence pesantren material structure studies, education and learning strategies as well as management and leadership that is able to make the schools persist in their characteristics, and also provide additional opportunities for the study of the material process of adaptation to the needs in the community. As a result, traditional pesantren alumni possess the character but modernist in addressing the changes and developments.